Design, synthesis and antibacterial evaluation of novel C-11, C-9 or C-2′-substituted 3-O-descladinosyl-3-ketoclarithromycin derivatives. (1st July 2021) - Bai, Bingfang; Bi, Fangchao; Qin, Yinhui; Teng, Yuetai; Ma, Shutao
Graphical abstract: Highlights: Novel 3- O -descladinosyl-3-keto-clarithromycin derivatives were synthesized and evaluated. Some of them showed effective activity against resistant strains. Compound 9b exhibited prominent antibacterial activity. Abstract: A novel series of 3- O -descladinosyl-3-keto-clarithromycin derivatives, including 11- O -carbamoyl-3- O -descladinosyl-3-keto-clarithromycin derivatives and 2′, 9(S)-diaryl-3- O -descladinosyl-3-keto-clarithromycin derivatives, were designed, synthesized and evaluated for their in vitro antibacterial activity. Among them, some derivatives were found to have activity against resistant bacteria strains. In particular, compound 9b showed not only the most significantly improved activity (16 µg/mL) against S. aureus ATCC43300 and S. aureus ATCC31007, which was >16-fold more active than that of CAM and AZM, but also the best activity against S. pneumoniae B1 and S. pyogenes R1, with MIC values of 32 and 32 µg/mL. In addition, compounds 9a, 9c, 9d and 9g exhibited the most effective activity against S. pneumoniae AB11 with MIC values of 32 or 64 µg/mL as well. Unfortunately, 2′, 9(S)-diaryl-3- O -descladinosyl-3-keto-clarithromycin derivatives failed to exhibit better antibacterial activity than references. It can be seen that the combined modification of the C-3 and C-11 positions of clarithromycin is beneficial to improve activity against resistant bacteria, while the single modification of the C-2′' position is very detrimental to antibacterial activity.